Portland cement for resource utilization of steel slag and preparation method of Portland cement
Through the grafting treatment of modified steel slag, the compressive strength and durability of silicate cement are improved, and the problem of reducing compressive strength caused by directly replacing clinker with steel slag is solved, achieving efficient resource recycling and environmental friendliness Silicate cement production.
Patent Information
- Application Number
- CN202411835346.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-11
AI Technical Summary
When the part of the silicate cement clinker is replaced directly with steel slag, it is easy to cause the compressive strength of the silicate cement to decrease, affecting its use.
Using modified steel slag, 3-trimethoxysilane propyl acrylate, calcium undecyl acrylate, 3-((2-(acryloyloxy)ethyl)dimethylammonium) propane- 1-Sulphonic acid internal salt, and introduce silicon oxy, calcium oxy, ester, sulfonic acid, and quaternary ammonium groups to improve the dispersion and binding force of modified steel slag, form a stable network structure, and improve the pressure resistance of silicate cement Strength and durability.
The 28d compressive strength of silicate cement is improved by > 63MPa and 7d hydration heat < 220kJ/kg, reducing the occurrence of cracks, extending the service life, and meeting market demand.
Smart Images

Figure BDA0005186548080000071 
Figure BDA0005186548080000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of steel slag recycling, and more specifically, to a silicate cement for recycling steel slag and a preparation method thereof. Background Art
[0002] Steel slag is a solid waste generated during the steel production process. With the rapid development of the steel industry, the emission of steel slag continues to increase. If the steel slag is piled up, it will not only occupy land resources but also pollute the environment. How to effectively utilize steel slag and realize resource recycling has become one of the important research topics.
[0003] In recent years, steel slag has been used more and more widely in building materials, especially in the production of Portland cement. The raw materials of Portland cement generally include Portland cement clinker and gypsum. Replacing part of the Portland cement clinker with steel slag can achieve the recycling of steel slag, improve resource utilization and reduce environmental pollution. However, the applicant found that directly replacing part of the Portland cement clinker with steel slag to obtain Portland cement can easily lead to a decrease in the compressive strength of Portland cement, affecting the use of Portland cement. Summary of the invention
[0004] On the basis of replacing part of the Portland cement clinker with steel slag, in order to improve the compressive strength of Portland cement, the present application provides a Portland cement utilizing steel slag as a resource and a preparation method thereof.
[0005] In the first aspect, the present application provides a silicate cement for the resource utilization of steel slag, adopting the following technical scheme: a silicate cement for the resource utilization of steel slag, the silicate cement is mainly made of the following raw materials in parts by weight: 50-60 parts of silicate cement clinker, 25-35 parts of modified steel slag, 4-6 parts of silicate, 3-5 parts of fly ash, 3-5 parts of desulfurized gypsum, and 1-3 parts of additives; the modified steel slag is obtained by treating the steel slag with 3-trimethoxysilane acrylate, calcium undecylenate, and 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt.
[0006] The silicate cement of the steel slag resource utilization of the present application adds steel slag to the raw materials to realize the recycling of steel slag, improve resource utilization, reduce environmental pollution, and is conducive to the recycling and sustainable development of resources. In addition, the steel slag is modified, and the interaction between it and the raw materials is utilized to make the 28d compressive strength of the silicate cement greater than 63MPa and the 7d hydration heat less than 220kJ / kg, showing the advantages of high compressive strength and low hydration heat, reducing the cracking caused by the temperature difference between the inside and the outside, improving durability and service life, and meeting market demand.
[0007] The modified steel slag in the silicate cement of the present application has 3-trimethoxysilane acrylate, calcium undecylenate, and 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt grafted on the surface of the steel slag, and siloxy, calcium oxy, ester, sulfonic acid, and quaternary ammonium groups are introduced to improve the dispersibility and bonding strength of the modified steel slag, and form a stable network structure, thereby increasing the compressive strength of silicate cement, reducing hydration heat, reducing cracks, improving crack resistance, improving durability, and extending service life. At the same time, silicates are added to the raw materials, which can enhance the fluidity of silicate cement, fill pores, increase density, improve microstructure, reduce internal defects, reduce hydration heat, and improve compressive strength, so that silicate cement exhibits better comprehensive performance.
[0008] Optionally, the modified steel slag is prepared by the following method: S1. Add steel slag to water under constant stirring at a temperature of 40-60°C, then add 3-trimethoxysilane acrylate, stir for 30-50 minutes, filter, and obtain a solid; S2. Add solid matter to ethanol under constant stirring at a temperature of 40-60°C, mix, then add calcium undecylenate and 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt, stir for 10-30 minutes, then dropwise add organic peroxide, after the dropwise addition is completed, stir for 1-3 hours, filter, wash, and dry to constant weight to obtain modified steel slag.
[0009] Optionally, the weight ratio of the steel slag, 3-trimethoxysilane acrylate, calcium undecylenate, 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt, and organic peroxide is 100:(20-30):(7-9):(7-9):(0.3-0.7).
[0010] By adopting the above technical scheme, in the aqueous phase, 3-trimethoxysilane acrylate is first grafted on the surface of the steel slag, and a carbon-carbon double bond is introduced to obtain a solid. Then, in the organic phase, calcium undecylenate and 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt are grafted on the surface of the solid to achieve grafting and obtain modified steel slag. The preparation method of the present application is adopted to ensure the stability of the preparation of the modified steel slag, and to increase the dispersibility and interfacial bonding strength of the modified steel slag, improve the fluidity and microstructure of silicate cement, enhance the use effect of the modified steel slag, improve the compressive strength of silicate cement, reduce the occurrence of cracks, and extend the service life.
[0011] Optionally, the organic peroxide is one or more of tert-butyl perpivalate, tert-butyl perbenzoate, dibenzoyl peroxide, and diisopropyl peroxydicarbonate.
[0012] By adopting the technical solution, the organic peroxide is optimized, which facilitates the selection of the organic peroxide.
[0013] Optionally, the weight ratio of the steel slag to water is 1:(7-13). In multiple implementation schemes, the weight ratio of the steel slag to water is 1:10, and the weight ratio can also be set to 1:7, 1:8, 1:9, 1:11, 1:12, 1:13 as needed, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0014] Optionally, the weight ratio of the steel slag to the ethanol is 1:(7-13). In multiple embodiments, the weight ratio of the steel slag to the ethanol is 1:10, and the weight ratio can also be set to 1:7, 1:8, 1:9, 1:11, 1:12, 1:13 as needed, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0015] Optionally, the organic peroxide is added dropwise for 20-40 minutes.
[0016] By adopting the above technical solution, the dropping time of the organic peroxide is optimized to ensure the stability of the preparation of the modified steel slag. In multiple embodiments, the dropping time of the organic peroxide is 30 minutes, and the dropping time can also be set to 20 minutes, 25 minutes, 35 minutes, and 40 minutes as needed, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0017] Optionally, the average particle size of the steel slag used in the modified steel slag is 10-20 μm.
[0018] By adopting the above technical solution, the particle size of the steel slag is limited, thereby achieving the limitation of the particle size of the modified steel slag, increasing the uniformity of the modified steel slag dispersion, and improving the use effect of the modified steel slag. In multiple implementation schemes, the average particle size of the steel slag is 15 μm, and the average particle size can also be set to 10 μm, 13 μm, 17 μm, 20 μm as needed, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0019] Optionally, the density of the slag is 2.8-3.3g / m 3 , specific surface area is 400-600m 2 / kg. In various embodiments, the density of the slag is 3.1 g / m 3 , specific surface area is 480m 2 / kg, and the density can also be set to 2.8g / m 3 , 2.9g / m3 , 3g / m 3 3.2g / m 3 3.3g / m 3 The specific surface area can also be set to 400m 2 / kg, 450m 2 / kg、500m 2 / kg, 550m 2 / kg、600m 2 / kg, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] Optionally, the silicate is one or both of tricalcium silicate and dicalcium silicate.
[0021] By adopting the above technical solution, silicate cement is optimized, which facilitates the selection of silicate cement. Moreover, tricalcium silicate and dicalcium silicate can increase fluidity, fill pores, increase density, improve microstructure, increase the compressive strength of silicate cement, and reduce the hydration heat of silicate cement, so that silicate cement exhibits better comprehensive performance.
[0022] Optionally, the silicate is tricalcium silicate and dicalcium silicate, and the weight ratio of tricalcium silicate to dicalcium silicate is (1-3):(1-3). In multiple embodiments, the weight ratio of tricalcium silicate to dicalcium silicate is 2:1, and the weight ratio can also be set to 1:1, 1:2, 1:3, 2:3, 3:1, 3:2 as needed, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] Optionally, the additive is one or more of a retarder, an accelerator, an early strength agent, and a water reducing agent.
[0024] By adopting the above technical solution, the additives are optimized and the selection of additives is convenient. Moreover, the retarder can prolong the setting time of silicate cement, which is beneficial for transportation and improves construction efficiency; the accelerator can accelerate the hydration reaction of silicate cement, shorten the setting time, accelerate solidification and molding; the early strength agent can improve the early compressive strength of silicate cement and accelerate the construction progress; the water reducer can reduce the water consumption, improve the fluidity and density, and improve the mechanical properties and durability of silicate cement.
[0025] Optionally, the additive is a retarder, and the retarder is one or more of citric acid, glycerol, glucose, and calcium lignin sulfonate.
[0026] By adopting the above technical scheme, the retarder is optimized, which facilitates the selection of the retarder. Moreover, citric acid, propylene glycol, glucose, and calcium lignin sulfonate can effectively prolong the setting time, improve the operability of the construction, and facilitate the construction.
[0027] Optionally, the retarder is citric acid and glucose, and the weight ratio of citric acid to glucose is (1-3):(1-3). In multiple embodiments, the weight ratio of citric acid to glucose is 1:2, and the weight ratio can also be set to 1:1, 1:3, 2:1, 2:3, 3:1, 3:2 as needed, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0028] In a second aspect, the present application provides a method for preparing silicate cement by recycling steel slag, which adopts the following technical solution: A method for preparing silicate cement by recycling steel slag mainly comprises the following steps: The silicate cement clinker, modified steel slag, fly ash, silicate, desulfurized gypsum and additives are mixed to obtain silicate cement.
[0029] By adopting the above technical solution, the preparation of silicate cement is facilitated.
[0030] In summary, this application has at least the following beneficial effects: 1. The silicate cement for resource utilization of steel slag in the present application realizes the recycling of steel slag through the mutual coordination between raw materials, improves resource utilization, reduces environmental pollution, is conducive to the recycling and sustainable development of resources, and has a 28d compressive strength of >63MPa and a 7d hydration heat of <220kJ / kg, showing the advantages of high compressive strength and low hydration heat, reducing cracking, improving durability and service life, and meeting market demand.
[0031] 2. The modified steel slag of the present application is first grafted with 3-trimethoxysilane acrylate on the surface of the steel slag, and then calcium undecylenate and 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid salt are grafted by polymerization reaction to obtain modified steel slag, and siloxy groups, calcium oxy groups, ester groups, sulfonic acid groups, and quaternary ammonium groups are introduced on the surface of the steel slag to improve the dispersibility, bonding force, and compatibility of the modified steel slag, increase fluidity and density, enhance network structure, improve microstructure, increase the compressive strength of silicate cement, reduce hydration heat, reduce cracks, improve crack resistance, enhance durability, and extend service life. DETAILED DESCRIPTION
[0032] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.
[0033] Preparation Example Preparation Example 1 A modified steel slag is prepared by the following method: S1. Add 100 g of steel slag to 1000 g of water at a rotation speed of 500 r / min and a temperature of 50°C, and stir for 10 min. Then add 25 g of 3-trimethoxysilane acrylate, stir for 40 min, and filter to obtain a solid.
[0034] The steel slag is carbon steel converter slag, with an average particle size of 15 μm and a density of 3.1 g / m 3 , specific surface area is 480m 2 / kg.
[0035] S2, at a speed of 500r / min and a temperature of 50°C, add the solid obtained in step S1 to 1000g of ethanol and stir for 10min. Then add 8g of calcium undecylenate and 8g of 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt and stir for 20min. Then drop 0.5g of organic peroxide, the drop time of organic peroxide is 30min, and after the drop addition is completed, stir for 2h. Then filter, wash three times with 50% ethanol aqueous solution, each time washing with 300g of ethanol aqueous solution, dry to constant weight, and obtain modified steel slag.
[0036] Wherein, the organic peroxide is tert-butyl peroxypivalate.
[0037] Preparation Example 2 A modified steel slag, which is different from Preparation Example 1 in that the added amounts of 3-trimethoxysilane propyl acrylate, calcium undecylenate, 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt and organic peroxide are different, and the added amount of 3-trimethoxysilane propyl acrylate is 20g, the added amount of calcium undecylenate is 9g, the added amount of 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt is 7g, and the added amount of organic peroxide is 0.3g.
[0038] Preparation Example 3 A modified steel slag, which is different from Preparation Example 1 in that the added amounts of 3-trimethoxysilane propyl acrylate, calcium undecylenate, 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt and organic peroxide are different, and the added amount of 3-trimethoxysilane propyl acrylate is 30g, the added amount of calcium undecylenate is 7g, the added amount of 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt is 9g, and the added amount of organic peroxide is 0.7g. Example
[0039] Table 1 Raw material dosage of Portland cement (unit: ×10g) Example Example 1 Example 2 Example 3 Portland cement clinker 55 50 60 Modified steel slag 30 35 25 Silicate 5 6 4 Fly ash 4 3 5 Desulfurization gypsum 4 5 3 Adding additives 2 1 3 total 100 100 100 Example 1 A silicate cement for recycling steel slag, the raw materials and raw material ratios of which are shown in Table 1.
[0040] Among them, C in Portland cement clinker 3 The S content is 38wt%, C 2 The S content is 42wt%, C 3 A content is 3wt%, C 4 The AF content is 15wt%; the silicates are tricalcium silicate and dicalcium silicate, and the weight ratio of tricalcium silicate to dicalcium silicate is 2:1; the fly ash is Class I fly ash; the desulfurized gypsum is selected from Shijiazhuang Deze Mineral Products Co., Ltd.; the added additives are retarders, and the retarders are citric acid and glucose, and the weight ratio of citric acid to glucose is 1:2; the modified steel slag is prepared by the method of Preparation Example 1.
[0041] A method for preparing silicate cement by recycling steel slag mainly comprises the following steps: Modified steel slag, silicate, fly ash, desulfurized gypsum and additives are added to silicate cement clinker and stirred for 5 minutes to obtain silicate cement.
[0042] Example 2 A silicate cement for recycling steel slag is different from Example 1 in that the raw material ratio of the silicate cement is different, and the raw material ratio of the silicate cement is shown in Table 1.
[0043] Example 3 A silicate cement for recycling steel slag is different from Example 1 in that the raw material ratio of the silicate cement is different, and the raw material ratio of the silicate cement is shown in Table 1.
[0044] Example 4 A silicate cement utilizing steel slag as a resource, which differs from Example 1 in that the modified steel slag in the raw materials of the silicate cement has a different source, and the modified steel slag is prepared by the method of Preparation Example 2.
[0045] Example 5 A silicate cement utilizing steel slag as a resource, which differs from Example 1 in that the modified steel slag in the raw materials of the silicate cement has a different source, and the modified steel slag is prepared by the method of Preparation Example 3.
[0046] Example 6 A silicate cement for recycling steel slag, which is different from Example 1 in that the silicate in the raw material of the silicate cement is tricalcium silicate.
[0047] Example 7 A silicate cement for recycling steel slag, which is different from Example 1 in that the silicate in the raw material of the silicate cement is dicalcium silicate.
[0048] Comparative Example Comparative Example 1 A silicate cement using steel slag as a resource is different from Example 1 in that an equal amount of steel slag is used to replace modified steel slag in the raw materials of the silicate cement.
[0049] Comparative Example 2 A silicate cement for recycling steel slag, which differs from Example 1 in that in the raw materials of the silicate cement, in the modified steel slag preparation method, an equal amount of 3-trimethoxysilane acrylate is used to replace calcium undecylenate and 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt.
[0050] Comparative Example 3 A silicate cement for recycling steel slag, which differs from Example 1 in that, in the raw materials of the silicate cement, in the modified steel slag preparation method, an equal amount of calcium undecylenate is used to replace 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt.
[0051] Comparative Example 4 A silicate cement for recycling steel slag, which differs from Example 1 in that in the raw materials of the silicate cement, in the modified steel slag preparation method, an equal amount of 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt is used to replace calcium undecylenate.
[0052] Comparative Example 5 A silicate cement for recycling steel slag, which differs from Example 1 in that silicate is replaced by an equal amount of silicate cement clinker in the raw materials of the silicate cement.
[0053] Performance Testing The silicate cement obtained in Examples 1-7 and Comparative Examples 1-5 was taken respectively, and the following performance tests were performed on the silicate cement. The test results are shown in Table 2.
[0054] Among them, compressive strength test: According to GB / T17671-2021 "Test method for strength of cement mortar (ISO method)", the 3d compressive strength and 28d compressive strength of silicate cement are tested.
[0055] Hydration heat detection: GB / T12959-2008 "Method for determination of hydration heat of cement" tests the 3d hydration heat and 7d hydration heat of Portland cement.
[0056] Table 2 Test results As can be seen from Table 2, the silicate cement of the present application has a high compressive strength, and the 3d compressive strength is 33.7-36.7MPa, and the 28d compressive strength is 63.5-67.5MPa, showing the advantage of high compressive strength. It also has a low hydration heat, 3d hydration heat is 163-179kJ / kg, and 7d hydration heat is 201-218kJ / kg, showing the advantage of low hydration heat, reducing the occurrence of cracking, improving durability, and meeting market demand.
[0057] Comparative Examples 1-2 are compared. Comparative Example 1 adds steel slag to the raw material of silicate cement; Comparative Example 2 adds modified steel slag to the raw material of silicate cement, and uses 3-trimethoxysilane acrylate to treat the steel slag. It can be seen that grafting and modifying steel slag can improve the use effect of modified steel slag, improve compressive strength, and reduce hydration heat. Combined with Comparative Examples 3-4 and Example 1. Comparative Example 3: Modified steel slag is added to the silicate cement raw material, and the steel slag is treated with 3-trimethoxysilane acrylate and calcium undecylenate to obtain the product; Comparative Example 4: Modified steel slag is added to the silicate cement raw material, and the steel slag is treated with 3-trimethoxysilane acrylate and 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt to obtain the product; Example 1: Modified steel slag is added to the silicate cement raw material, and the steel slag is treated with 3-trimethoxysilane acrylate, calcium undecylenate and 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt to obtain the product. It can be seen that on the basis of grafting 3-trimethoxysilane acrylate on the surface of steel slag, calcium undecylenate and 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt are further grafted, and calcium oxygen group, ester group, sulfonic acid group and quaternary ammonium group are introduced on the surface of steel slag, which can enhance the binding force, compatibility and dispersibility of the modified steel slag, further improve the compressive strength of silicate cement, and reduce the hydration heat of silicate cement.
[0058] Comparative Example 5, Examples 6-7, and Example 1 are compared. In Comparative Example 5, no silicate is added to the raw material of silicate cement; in Example 6, silicate is added to the raw material of silicate cement, and the silicate is tricalcium silicate; in Example 7, silicate is added to the raw material of silicate cement, and the silicate is dicalcium silicate; in Example 1, silicate is added to the raw material of silicate cement, and the silicate is tricalcium silicate and dicalcium silicate. It can be seen from this that adding tricalcium silicate and dicalcium silicate to the raw materials at the same time and utilizing the synergistic effect between them can not only enhance the fluidity of silicate cement, but also fill the pores, increase the density, enhance the network structure, improve the compressive strength, and reduce the hydration heat, so that silicate cement exhibits better comprehensive performance.
[0059] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.
Claims
1. A silicate cement for recycling steel slag, characterized by: The silicate cement is mainly prepared from the following raw materials in parts by weight: 50-60 parts of silicate cement clinker, 25-35 parts of modified steel slag, 4-6 parts of silicate, 3-5 parts of fly ash, 3-5 parts of desulfurized gypsum and 1-3 parts of additives; the modified steel slag is obtained by treating the steel slag with 3-trimethoxysilane acrylate, calcium undecylenate and 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt.
2. The silicate cement for recycling steel slag according to claim 1, characterized in that: The modified steel slag is prepared by the following method: S1. Add steel slag to water under constant stirring at a temperature of 40-60°C, then add 3-trimethoxysilane acrylate, stir for 30-50 minutes, filter, and obtain a solid; S2. Add solid matter to ethanol under constant stirring at a temperature of 40-60°C, mix, then add calcium undecylenate and 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt, stir for 10-30 minutes, then dropwise add organic peroxide, after the dropwise addition is completed, stir for 1-3 hours, filter, wash, and dry to constant weight to obtain modified steel slag.
3. The silicate cement for recycling steel slag according to claim 2, characterized in that: The weight ratio of the steel slag, 3-trimethoxysilane acrylate, calcium undecylenate, 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonic acid inner salt, and organic peroxide is 100:(20-30):(7-9):(7-9):(0.3-0.7).
4. The silicate cement for recycling steel slag according to claim 2, characterized in that: The organic peroxide is one or more of tert-butyl perpivalate, tert-butyl perbenzoate, dibenzoyl peroxide, and diisopropyl peroxydicarbonate.
5. The silicate cement for recycling steel slag according to claim 2, characterized in that: The organic peroxide is added dropwise for 20-40 minutes.
6. The silicate cement for recycling steel slag according to claim 1, characterized in that: The average particle size of the steel slag used in the modified steel slag is 10-20 μm.
7. The silicate cement for recycling steel slag according to claim 1, characterized in that: The silicate is one or both of tricalcium silicate and dicalcium silicate.
8. The silicate cement for recycling steel slag according to claim 1, characterized in that: The silicates are tricalcium silicate and dicalcium silicate, and the weight ratio of tricalcium silicate to dicalcium silicate is (1-3):(1-3).
9. The silicate cement for recycling steel slag according to claim 1, characterized in that: The additive is one or more of a retarder, an accelerator, an early strength agent, and a water reducing agent.
10. A method for preparing silicate cement by recycling steel slag as claimed in any one of claims 1 to 9, characterized in that: The main steps are as follows: The silicate cement clinker, modified steel slag, silicate, fly ash, desulfurized gypsum and additives are mixed to obtain silicate cement.